2019
DOI: 10.1002/adom.201900364
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Recyclable Upconversion‐Fluorescence Fibrous Indicator Paper with Plasmonic Nanostructures for Single Droplet Detection

Abstract: attention due to their extensive biological and medical applications. [1][2][3][4][5] Conventional indicator paper such as pH paper is disposable after use. Similarly, a traditional particulate-based fluorescence sensor is also not reusable because it usually suspends fluorescent nanoparticles such as quantum dots and upconversion nanocrystals in the target solution to initiate detection, [6][7][8][9] which are often unstable and irreproducible when contaminated by the target solution. Additionally, these indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Various efforts have been devoted to elevating the FRET efficiency of UC luminescence nanoprobes by prolonging the effective FRET distance or shortening the distance between the acceptor and donor. As an effective strategy for lengthening the FRET work distance, Au nanoparticles and carbon nanomaterials with a dipole-surface effect were explored as energy acceptors to activate FRET over 20 nm. , However, the interface instability of UCNPs and Au or carbon nanomaterials has limited the detection accuracy. Most recently, Liu et al demonstrated a 30 nm Gd 3+ -mediated long-range energy migration nanosystem for an efficient FRET process which mitigated the particle size constraint .…”
Section: Introductionmentioning
confidence: 99%
“…Various efforts have been devoted to elevating the FRET efficiency of UC luminescence nanoprobes by prolonging the effective FRET distance or shortening the distance between the acceptor and donor. As an effective strategy for lengthening the FRET work distance, Au nanoparticles and carbon nanomaterials with a dipole-surface effect were explored as energy acceptors to activate FRET over 20 nm. , However, the interface instability of UCNPs and Au or carbon nanomaterials has limited the detection accuracy. Most recently, Liu et al demonstrated a 30 nm Gd 3+ -mediated long-range energy migration nanosystem for an efficient FRET process which mitigated the particle size constraint .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve in situ melt e-spinning, the conventional melt e-spinning device is an option [20][21][22][23][24][25][26][27][28][29][30][31]. However, these conventional melt e-spinning devices usually use a heating method such as resistance wires [22,23], laser heating [24,25], microwave heating [26], heated air and oil liquid [26][27][28][29][30][31] which need mains supply to melt the polymer for subsequent e-spinning, which is inconvenient in practical clinical and practical applications, especially where is no mains supply in the wild outdoors. In order to solve the problem of relying on the mains supply, the previous research used heating methods such as alcohol lamps, candles, etc.…”
Section: Introductionmentioning
confidence: 99%
“…33 1.5. Compósitos poliméricos com conversão ascendente Compósitos que apresentam conversão ascendente tem grande destaque na literatura, principalmente na área biomédica junto à teranósticos 25,34 , termômetros 35 e energias alternativas 19 . O uso de UCNps em polímeros é recorrente, sendo primariamente utilizados em sistemas eletrofiados 36 .…”
unclassified